Transformation of legal consciousness as a threat to the cybersecurity of an individual - Brovkina Alexandra; Burukin Vadim; Makarova Valentina; Trifonova Tatiana (BIO Web of Conferences, 2023)
The widespread availability of information and telecommunication sources (IT technologies), on the one hand, increases the level of legal awareness of the population and the effectiveness of interaction between political institutions and civil society, the activities of state bodies are becoming more transparent, education is more accessible. But in parallel with this, the level of the destructive impact of digitalization of public relations is also growing. A person dissolves into virtual reality, the personality is split into two, i.e. realized and manifested at different levels in different ways in virtual and real reality, there is a transformation of consciousness and, as a consequence of legal consciousness. In our opinion, the above provision is an urgent problem and requires theoretical and legal analysis. The article examines the problems of transformation of the legal consciousness of an individual in the digital space. The authors propose measures aimed at reducing the unfavorable factors affecting the distortion of legal consciousness.